Investigating obesity‐related risk factors for childhood asthma. Issue 1 (14th December 2021) - Chen, Yang‐Ching; Su, Ming‐Wei; Brumpton, Ben M.; Lee, Yungling L.
Abstract: Background: We tested the hypothesis that multiple obesity‐related risk factors (obesity, physical activity, cardiopulmonary physical fitness, sleep‐disorder breathing (SDB), and sleep quality) are associated with childhood asthma using a Mendelian randomization (MR) design. Furthermore, we aim to investigate whether these risk factors were associated with incident asthma prospectively. Methods: In total, 7069 children aged 12 from the Taiwan Children Health Study were enrolled in the current study. Cross‐sectional logistic regression, one‐sample MR, summary‐level MR sensitivity analyses, and prospective survival analyses were used to investigate each causal pathway. Results: In MR analysis, three of the five risk factors (obesity, SDB, and sleep quality) were associated with asthma, with the highest effect sizes per inter‐quartile range (IQR) increase observed for sleep quality (odds ratio [OR] = 1.42; 95% confidence interval [CI]: 1.06 to 1.92) and the lowest for obesity (OR = 1.08; 95% CI: 1.00–1.16). In the prospective survival analysis, obesity showed the highest risk of incident asthma per IQR increase (hazard ratio [HR] = 1.28; 95% CI: 1.05 to 1.56), followed by SDB (HR = 1.18; 95% CI: 1.08 to 1.29) and sleep quality (HR = 1.10; 95% CI: 1.03 to 1.17). Conclusion: Among the examined factors, the most plausible risk factors for asthma were obesity, SDB, and poor sleep quality. For the prevention of childhood asthma, relevant stakeholders should prioritize improving children's sleep quality and preventing obesity comorbidities such as SDB.